2020
DOI: 10.1136/bjsports-2019-101584
|View full text |Cite
|
Sign up to set email alerts
|

Rib stress injuries in the 2012–2016 (Rio) Olympiad: a cohort study of 151 Australian Rowing Team athletes for 88 773 athlete days

Abstract: AimTo describe the demographics, frequency, location, imaging modality and clinician-identified factors of rib stress injury in a cohort of elite rowers over the Rio Olympiad (2012–2016).MethodsAnalysis of prospectively recorded medical records for the Australian Rowing Team in 2013–2015 and the combined Australian Rowing Team and Olympic Shadow Squad in 2016, examining all rib stress injuries.Results19 rib stress injuries (12 reactions and 7 fractures) were identified among a cohort of 151 athletes and includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…1,2,4,39,50 The rates of athletes who returned to sports varied from 61.9% to 100%. In particular, 4 studies reported a 100% rate of return to sports for all MRI grades of injury, 1,4,22,50 and 2 studies (participants were military recruits) reported a subset of the population that did not return to their preinjury status. 8,51 Specifically, no correlation between injury grade and return to sports was observed by Chalupa et al 8 In contrast, Rohena-Quinquilla et al 51 reported a significantly higher discharge rate in high-grade femoral neck stress injuries (grade 1: 2.7%; grade 2: 3.7%; grade 3: 10%; grade 4: 38.1%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,4,39,50 The rates of athletes who returned to sports varied from 61.9% to 100%. In particular, 4 studies reported a 100% rate of return to sports for all MRI grades of injury, 1,4,22,50 and 2 studies (participants were military recruits) reported a subset of the population that did not return to their preinjury status. 8,51 Specifically, no correlation between injury grade and return to sports was observed by Chalupa et al 8 In contrast, Rohena-Quinquilla et al 51 reported a significantly higher discharge rate in high-grade femoral neck stress injuries (grade 1: 2.7%; grade 2: 3.7%; grade 3: 10%; grade 4: 38.1%).…”
Section: Resultsmentioning
confidence: 99%
“…The data from 9 studies were used for meta-analysis. 1,2,4,22,34,39,48,50,51 A further 7 studies were included in the systematic review but not meta-analysis, as specific return-to-sports data for each injury grade were missing. 8,13,16,37,44,49,62 Meta-analyses were performed to summarize the mean time to return to sports for MRI grades 1 to 4 (7 studies) and to compare low- with high-grade injuries (8 studies).…”
Section: Methodsmentioning
confidence: 99%
“…Upper extremity bone stress injuries are less common, but have been reported in many different athletes, including rowers, weightlifters, gymnasts, swimmers, golfers, and pitchers. [3][4][5][6] Bone stress injuries in throwing athletes generally occur around the shoulder girdle and trunk, and have been reported in the clavicle, ribcage (primarily 1st rib), humerus, olecranon, and ulna. 5 Case reports of rib stress injuries in pitchers indicate that the first rib may be the most common site in the ribcage, with injuries at the lower ribs less commonly reported.…”
Section: Introductionmentioning
confidence: 99%
“…Though lower rib BSIs are common in rowers (ribs 4-8 accounting for around 80%), stress injuries of ribs 2-12 are rarely reported in pitchers, but may be largely underrecognized. 4,7,[27][28][29] Case reports describe injuries at ribs 7-9, as well as the floating ribs (ribs 11-12). 28,29 Bone stress injuries occurring between ribs 7-9 have been attributed to the opposing anterior/caudad rotational force of the external oblique muscles and posterior/cephalad force of the serratus anterior.…”
mentioning
confidence: 99%
“…Therefore, there is interest in addressing other mechanisms by which bone metabolism may be perturbed. Elite rowers typically present with normal areal bone mineral density (aBMD) relative to general population norms; however, this may be inadequate to withstand the load required by the sport ( 9 ) and may be associated with history of bone stress injury of the rib ( 10 ), associated with significant training time loss and performance decrement ( 11 ).…”
mentioning
confidence: 99%